A weight of evidence framework for environmental assessments: Inferring quantities. (21st July 2017) - Suter, Glenn; Cormier, Susan; Barron, Mace
ABSTRACT: The US Environmental Protection Agency (USEPA) has developed a generally applicable framework for a weight‐of‐evidence (WoE) process for deriving quantitative values from multiple estimates. These guidelines are intended for environmental assessments that require the generation of quantitative parameters such as degradation rates or that develop quantitative products such as criterion values or magnitudes of effects. The basic steps are to weigh evidence for the environmental quality to be quantified, generate the value by merging estimates or by identifying the best estimate, and weight the results to determine confidence in the numerical value. When multiple data sets or outputs of multiple models are available, it may be appropriate to weigh the evidence. Use of the framework to weigh multiple estimates may increase the accuracy of quantitative results compared to a single estimate from a default method. Its use can provide greater transparency compared to ad hoc weighing of evidence. Integr Environ Assess Manag 2017;13:1045–1051. Published 2017. This article is a US Government work and is in the public domain in the USA. Key Points: Heterogeneous evidence can be weighed to derive quantities such as water quality criteria or magnitudes of effects in risk assessments. The quality to be quantified, such as the endpoint in a risk assessment, may be derived by weighing evidence. The quantity may be derived by a combining weighted estimates (meta analysis) or by weighing the alternative estimates to choose the best. Confidence in a final estimate is a result of both the statistical scatter and the qualitative weight of the estimate.